Effect of intracanal cryotherapy on postoperative pain control after endodontic therapy: a literature review - Guilherme Pauletto; Mariana De Carlo Bello (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2021)
Aim: The aim of this literature review is to investigate and critically analyze the use of intracanal cryotherapy during endodontic treatment and, through scientific findings, elaborate well grouded references that justify or not, carrying out such auxiliary protocol during endodontic intervention. Literature Review: The therapeutic alternative known as cryotherapy is a technique that has existed for years, which has been frequently applied in Medicine for the treatment of pain and postoperative care. Recently, the use of cryotherapy in Endodontics, through a final root canal irrigation protocol, has been examined in several randomized clinical trials. Discussion: The reviewed studies showed that the use of cold saline solution as a final irrigating agent for chemical-mechanical preparation has the potential to reduce pain levels of a possible painful symptomatology after endodontic treatment, in addition to being a method of easy application and low cost. Conclusion: Although there are few studies on the subject, scientific evidences available and reviewed in this article properly support the effect of intracanal cryotherapy in reducing the postoperative pain of an endodontic intervention. However, new studies should be placed to investigate possible harmful effects and to prepare a predictable and safe protocol.